Anak menjadi Korban Eksploitasi (Perkawinan Paksa) Oleh Orang Tua - Rozi, Achmad Fathur; Ahmad, Muh.Jufri (CV. Era Digital Nusantara, 2023)
The situation of children being used as collateral for debts is a common thing due to the inability of parents to pay the debt. This incident is also more common when debt involves loan sharks. This incident certainly requires government oversight. The writing method used is the normative juridical research method. The legal research methodology in question is research based on applicable laws and regulations as well as other documents relevant to the discussion as supporting research material. The research findings show that the Child Welfare Law treats guarantees for children who are subject to debt guarantees as a crime that violates the provisions of Article 76I juncto Article 88 because it is classified as an act of economic exploitation of children. The viewpoint of the Islamic religion is not much different from the provisions of national law. Judging from the agreement, the actions taken by the creditor in accepting children according to Islamic law are inappropriate, because they do not meet the requirements of the kafalah contract. Children are not legal objects because they are not assets that can be mortgaged, nor are they legal objects that can be used as collateral because children do not have legal authority. Keywords: Legal Protection,Exploitation,Children